2017
DOI: 10.1186/s12893-017-0308-9
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction in the third portion of the duodenum due to a diospyrobezoar: a case report

Abstract: BackgroundDuodenal obstruction occurs mainly due to physical lesions such as duodenal ulcers or tumors. Obstruction due to bezoars is rare. We describe an extremely rare case of obstruction in the third portion of the duodenum caused by a diospyrobezoar 15 months after laparoscopic distal gastrectomy for early gastric cancer.Case presentationA 73-year-old man who underwent laparoscopic distal gastrectomy for early gastric cancer 15 months before admission experienced abdominal distension and occasional vomitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Typically, they appear as single masses in the gastric fundus, with various colors (black, green, beige or other, according to composition). However, they may be multiple or very rarely be impacted in the esophagus or duodenum [4,48,49].…”
Section: Manifestations and Diagnostic Approachmentioning
confidence: 99%
“…Typically, they appear as single masses in the gastric fundus, with various colors (black, green, beige or other, according to composition). However, they may be multiple or very rarely be impacted in the esophagus or duodenum [4,48,49].…”
Section: Manifestations and Diagnostic Approachmentioning
confidence: 99%
“…Obstruction of the third portion of the duodenum secondary to a phytobezoar is a rare entity with limited documentation in the literature (Yamagata et al, 2017). Our case is noteworthy due to the site of obstruction and the absence of surgical history or exclusively vegetarian dietary patterns.…”
Section: Discussionmentioning
confidence: 81%
“…Phytobezoars located in the duodenum are extremely rare (Fan et al, 2016), with a reported incidence of less than 0.4% in the general population (Fan et al, 2016), and even rarer in the third portion of the duodenum (Yamagata et al, 2017).…”
Section: Discussionmentioning
confidence: 99%